The Effect of Ambient Temperature on Brachypodium distachyon Development - Li, Meixia; Kennedy, Alice; Huybrechts, Michiel; Dochy, Niklas; Geuten, Koen (Frontiers in Plant Science, 2019)
Due to climate change, the effect of temperature on crops has become a global concern. It has been reported that minor changes in temperature can cause large decreases in crop yield. While not a crop, the model Brachypodium distachyon can help to efficiently investigate ambient temperature responses of temperate grasses, which include wheat and barley. Here we use different accessions to explore the effect of ambient temperature on Brachypodium phenology. We recorded leaf initiation, heading time, leaf and branch number at heading, seed set time, seed weight, seed size, seed dormancy and seed germination at different temperatures. We found that warmer temperatures promote leaf initiation so that leaf number at heading is positively correlated to temperature. Heading time is not correlated to temperature but accessions show an optimal temperature at which heading is earliest. Cool temperatures prolong seed maturation which increases seed weight. The progeny seeds of plants grown at these cool ambient temperatures show stronger dormancy, while imbibition of seeds at low temperature improves germination. Among all developmental stages, it is the duration of seed maturation that is most sensitive to temperature. The results we found reveal that temperature responses in Brachypodium are highly conserved with temperate cereals, which makes Brachypodium a good model to explore temperature responsive pathways in temperate grasses.